Impact of creatinine methodology on glomerular filtration rate estimation in diabetes - Lovrenčić, Marijana Vučić (World J Diabetes, 2017)
AIM: To evaluate the influence of creatinine methodology on the performance of chronic kidney disease (CKD)-Epidemiology Collaboration Group-calculated estimated glomerular filtration rate (CKD-EPI-eGFR) for CKD diagnosis/staging in a large cohort of diabetic patients. METHODS: Fasting blood samples were taken from diabetic patients attending our clinic for their regular annual examination, including laboratory measurement of serum creatinine and eGFR. RESULTS: Our results indicated an overall excellent agreement in CKD staging (kappa = 0.918) between the Jaffé serum creatinine- and enzymatic serum creatinine-based CKD-EPI-eGFR, with 9% of discordant cases. As compared to the enzymatic creatinine, the majority of discordances (8%) were positive, i.e., associated with the more advanced CKD stage re-classification, whereas only 1% of cases were negatively discordant if Jaffé creatinine was used for eGFR calculation. A minor proportion of the discordant cases (3.5%) were re-classified into clinically relevant CKD stage indicating mildly to moderately decreased kidney function (< 60 mL/min per 1.73 m(2)). Significant acute and chronic hyperglycaemia, assessed as plasma glucose and HbA(1c) levels far above the recommended glycaemic goals, was associated with positively discordant cases. Due to a very low frequency, positive discordance is not likely to present a great burden for the health-care providers, while intensified medical care may actually be beneficial for the small number of discordant patients. On the other hand, a very low proportion of negatively discordant cases (1%) at the 60 mL/min per 1.73 m(2) eGFR level indicate a negligible possibility to miss the CKD diagnosis, which could be the most prominent clinical problem affecting patient care, considering high risk of CKD for adverse patient outcomes. CONCLUSION: This study indicate that compensated Jaffé creatinine procedure, in spite of the glucose-dependent bias, is not inferior to enzymatic creatinine in CKD diagnosis/staging and therefore may provide a reliable and cost-effective tool for the renal function assessment in diabetic patients.